An other-race effect for configural and featural processing of faces: upper and lower face regions play different roles - Wang, Zhe; Quinn, Paul C.; Tanaka, James W.; Yu, Xiaoyang; Sun, Yu-Hao P.; Liu, Jiangang; Pascalis, Olivier; Ge, Liezhong; Lee, Kang (Frontiers in Psychology, 2015)
We examined whether Asian individuals would show differential sensitivity to configural vs. featural changes to own- and other-race faces and whether such sensitivity would depend on whether the changes occurred in the upper vs. lower regions of the faces. We systematically varied the size of key facial features (eyes and mouth) of own-race Asian faces and other-race Caucasian faces, and the configuration (spacing) between the eyes and between the nose and mouth of the two types of faces. Results revealed that the other-race effect (ORE) is more pronounced when featural and configural spacing changes are in the upper region than in the lower region of the face. These findings reveal that information from the upper vs. lower region of the face contributes differentially to the ORE in face processing, and that processing of face race is influenced more by information location (i.e., upper vs. lower) than by information type (i.e., configural vs. featural).